Proactive treatment of atopic dermatitis in adults with 0.1% tacrolimus ointment - Wollenberg, A.; Reitamo, S.; Girolomoni, G.; Lahfa, M.; Ruzicka, T.; Healy, E.; Giannetti, A.; Bieber, T.; Vyas, J.; Deleuran, M. (Allergy (Copenhagen), 2008)
Background:  Long‐term treatment for atopic dermatitis (AD) using low dose, intermittent, topical anti‐inflammatory agents may control acute disease and prevent relapses. This 12‐month, European, multicentre, randomized study investigated whether the proactive use of 0.1% tacrolimus ointment applied twice weekly can keep AD in remission and reduce the incidence of disease exacerbations (DE). Methods:  During the initial open‐label period, 257 adults with AD applied 0.1% tacrolimus ointment twice daily (b.i.d.) for up to 6 weeks to affected areas. When an Investigator Global Assessment (IGA) score of ≤2 was achieved, the patient entered the disease control period (DCP) and was randomized to either proactive tacrolimus (n = 116) or vehicle ointment (n = 108) twice weekly for 12 months. Exacerbations were treated with 0.1% tacrolimus ointment b.i.d. until an IGA ≤2 was regained, then randomized treatment was restarted. The primary endpoint was the number of DEs during the DCP that required a substantial therapeutic intervention. Results:  Proactive tacrolimus 0.1% ointment application significantly reduced the number of DEs requiring substantial therapeutic intervention (median difference 2; P < 0.001; Wilcoxon rank sum test), the percentage of DE treatment days (median difference: 15.2%; P < 0.001; Wilcoxon rank sum test) and increased the time to first DE (median 142 vs 15 days; P < 0.001; stratified log‐rank test). The adverse event profile was similar for the two treatment approaches. Conclusion:  A 12‐month, twice weekly proactive tacrolimus ointment application was an effective treatment in most study patients which prevented, delayed and reduced the occurrence of AD exacerbations.